1995
DOI: 10.1002/elps.11501601348
|View full text |Cite
|
Sign up to set email alerts
|

Some variables affecting reproducibility in capillary electrophoresis

Abstract: Several variables that can affect reproducibility of both the peak height and the migration time in capillary electrophoresis (CE) were investigated here. A great part of the imprecision in CE for migration time is related to the interaction of the analyte with the capillary wall. Within a run, acidic compounds with long migration times have a higher relative standard deviation. In general, conditions that decreased the migration time, such as a short capillary length, tended to enhance the reproducibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 11 publications
4
36
0
Order By: Relevance
“…The reproducibility of the migration time (for peak identification) improves greatly if the calculation is based on an internal standard with a migration close to that of serum proteins. However, the reproducibility of the area (for albumin or y-gl.obulins) is not improved by using an internal standard similar to what we previously reported [21].…”
Section: Internal Standardssupporting
confidence: 57%
“…The reproducibility of the migration time (for peak identification) improves greatly if the calculation is based on an internal standard with a migration close to that of serum proteins. However, the reproducibility of the area (for albumin or y-gl.obulins) is not improved by using an internal standard similar to what we previously reported [21].…”
Section: Internal Standardssupporting
confidence: 57%
“…However, as Shibabi and Hinsdale [109] pointed out that the fast development in capillary electrophoresis has so far been focused on the improvement of resolution and throughput rather than reproducibility and absolute precision. One successful approach to improve the reproducibility of both mobility and integral data has been based on internal standards [110].…”
Section: Electrophoretic Methodsmentioning
confidence: 99%
“…Usually, the larger the area under the peak, the better the precision, especially for analytes at low concentration [8]. However, in spite of these conditions, we found the precision of the peak height to be much better than that of the area (Table 1) as has been found previously, mainly because of the integrator software [9]. Increasing the sample size to 20 s to further increase the peak area led to a decrease in precision due to the inadequate capillary wash of the excess adsorbed proteins.…”
Section: Resultsmentioning
confidence: 54%
“…The quantification of a minor small peak in the presence of a large one is problematic in most separation methods and especially CE. In CE, several factors affect the precision and accuracy of such quantification, e.g., sample size, wall interaction, integrator software, and voltage [9]. Here it is demonstrated that the major hemoglobin variants A, F, S, C, and A 2 can be separated well by CE in an arginine-Tris buffer.…”
Section: Introductionmentioning
confidence: 92%